Lingering mysteries in ritual enactments in Sparta and Laconia c.700-450 BC: lead figurines as protection against fear - Fragkopoulou, Florentia (Journal of Greek Archaeology, 2025)
This paper re-examines the use of lead figurines as symbolic objects in a variety of ritual enactments particular to individual sites. Irrespective of the details of each case, it is argued that the lead itself – its accessibility and the qualities attributed to it – defines the ritual power of these objects. The few scholars to discuss them see them as mundane items made of an accessible and cheap raw material. Thus, it is claimed, lead figurines were deposited en masse exclusively by Spartan citizens (and women) during some ritual or festival probably related to Spartan military identity. Lead figurines circulated from the 7th century until c.450 BC. Explanations for their abandonment have been sought in the growing use of lead from Laurion and the predominance of Attic pottery at sites across the Mediterranean. However, I prefer to focus on the rise and decline of a specific Laconian ritual habitus which employed ideological and material instruments related to their region, and endured for as long as it served local ritual needs. Furthermore, previous publications have left unaddressed the role of nocturnal rituals which were equally if not more frequent, depending upon the character of the divinity worshipped.